THE CONCEPT OF LIFELONG EDUCATION IN ISLAM - Hasan, Mawardi (Ar Raniry : International Journal of Islamic Studies, 2017)
Lifelong education is a concept of continuous learning from the cradle to the end of life, in line with the phases (stages) of human development. Education is a process that contains the spirit to bring hope to learners. Because humans have desires to do well and be advanced in various aspects of life, a practical level of education is really needed due to the fact that education is the most effective process for humans to meet those needs. Islam as the most perfect religion has the doctrine that human life takes place in two dimensions: the dimension of the world and the dimension of the hereafter. From such a vast scope of life, Islam offers an unlimited education which is practical and applicable.